2017
DOI: 10.1111/and.12767
|View full text |Cite
|
Sign up to set email alerts
|

Sperm RNA preparation for transcriptomic analysis: Review of the techniques and personal experience

Abstract: In the last 10 years, several approaches, including microarrays, have been applied to investigate sperm transcript levels. However, success using microarray profiling is highly dependent of the quality of the RNA obtained. Therefore, the development of methods that deliver highly purified and intact RNA is of utmost importance. The three steps used to achieve this goal, purification of spermatozoa, RNA extraction and evaluation of RNA quality, are reviewed. Following that review and preliminary experiments, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…1 e, inset). These data, together with immunofluorescence microscopy examination, indicate that these samples were almost devoid of non-sperm cells 36 .…”
Section: Resultsmentioning
confidence: 54%
“…1 e, inset). These data, together with immunofluorescence microscopy examination, indicate that these samples were almost devoid of non-sperm cells 36 .…”
Section: Resultsmentioning
confidence: 54%
“…Based on the computational formula of TPM, it is directly proportional to the number of transcripts. In addition, spermatozoa contained few or even no rRNA (Miller et al, 2005;Fang et al, 2014;El Fekih et al, 2017), which provides a favorable condition for the estimation of consistent transcripts. The average number of transcripts in each spermatozoon can be estimated based on TPM values and average RNA contents in each spermatozoon.…”
Section: Change Of Oxidation Resistance In Spermmentioning
confidence: 99%
“…A plethora of data exists on sperm RNAs using different species and different targets such as mRNA, piwiRNA and miRNA, however they all face similar technical difficulties due to the unique biology of the sperm itself [25, 41]. To this, recent studies have tried to establish a standard, across species, protocol to extract sperm RNA [18, 22, 24, 42]. Consequently, the development of standardized sperm RNA preparation and isolation methods to deliver highly purified and intact RNA is of absolute importance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of the ribosomal RNA in spermatozoa, spectral analysis of RNA abundance by size is still useful to assess sperm RNA quality and purity since the presence of the ribosomal subunits 18S and 28S may indicate somatic cell RNA contamination. A spermatozoon contains far less RNA than a somatic cell [11, 14, 42], and collection from rat epididymal fluid, as well as human ejaculate contain somatic cells along with spermatozoa; therefore, sperm purification in the RNA isolation protocol is an essential step. These observations are in conflict with a previous study that reported that ribosomal RNA 18S but not 28S is present in purified spermatozoa [19].…”
Section: Discussionmentioning
confidence: 99%